Simultaneous terpolymerization of CO2/SO2 with epoxide and mechanistic understanding. (28th February 2019) - Zhi, Yunfei; Miao, Yingju; Zhao, Wenbo; Wang, Junya; Zheng, Yane; Su, Hongying; Jia, Qingming; Shan, Shaoyun
Abstract: CO2 and SO2 appear simultaneously in most industrial cases and have caused serious environmental and health issues, however, the simultaneous conversion of SO2 and CO2 has not been reported until now. This work describes an alternating terpolymerization of SO2 /CO2 with cyclohexene oxide using SalenCr III Cl as catalyst and bis(triphenylphosphine)iminium chloride as cocatalyst, and a novel poly(cyclohexene carbonate sulfite) was obtained. The terpolymers were characterized by nuclear magnetic resonance spectroscopy, infrared spectroscopy, and gel permeation chromatography, and effects of the different reaction conditions on the structures of the terpolymers (carbonate content and sulfite content in the block copolymer) were investigated. In experiments, we found that SO2 not only acts as reactant, but also exhibits a nucleophilicity to promote the ability embedding of SO2 in the terpolymers. According to the study of mechanism that proposed by predecessors and experiment, the possible terpolymerization mechanisms are recommended. The results proved that the terpolymerization of CO2 /SO2 with epoxides may be considered as an effective approach to simultaneously convert CO2 and SO2, and improve efficiency of the CO2 /SO2 utilization. Graphical abstract: We found that SO2 and CO2 can simultaneously be terpolymerized with epoxid, and form a new poly(carbonate sulfite) with excellent properties. The possible terpolymerization mechanisms are recommended. The results proved that the terpolymerization of CO2 /SO2 with epoxides may be considered as an effective approach to simultaneously utilize CO2 and SO2 .Image 10384 Highlights: Employ SalenCr Ⅲ Cl catalyze SO2 copolymerize with epoxide. Employ SalenCr Ⅲ Cl catalyze epoxide terpolymerize with SO2 and CO2 . Mechanism understanding of terpolymeration of SO2, CO2 and epoxide. SO2 is reactant, also co-catalyst.